ANALISIS INDEKS HARGA KONSUMEN (IHK), INFLASI, DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI ACEH BARAT - Zelvika Dewi; Ratna Husein (LPPM UNIMAL, 2022)
This study examined the effect of the consumer price index (CPI), inflation, and population against poverty in West Aceh. This study used secondary data in the form of time-series data from 2001 to 2020. The analysis method used was a multiple linear regression with the help of E-views 10. The results partially indicated that the consumer price index positively and significantly affected poverty in West Aceh, inflation negatively and insignificantly affected poverty in West Aceh, and population negatively and significantly affected poverty in West Aceh. Simultaneously, the consumer price index, inflation, and population affected poverty in West Aceh with a probability value of 0.04.